Evaluation of methicillin-resistant Staphylococcus aureus infections in pemphigus vulgaris patients: cross-sectional study - Hanan F Mohamed (Journal of the Egyptian Women’s Dermatologic Society, 2020)
Background Pemphigus vulgaris (PV) is a potentially fatal autoimmune vesiculobullous disease. Staphylococcus aureus is the most common cause of cutaneous bacterial infection in pemphigus. Methicillin-resistant S. aureus (MRSA) is a common multidrug-resistant bacterium. MRSA infection is high among dermatology inpatients and vesiculobullous diseases patients are the commonest infected. Objective This study aimed at determining the causative organisms of the secondary bacterial skin infections in PV patients, identifying MRSA, doing antibiotic sensitivity pattern for MRSA, and determining the risk factors for acquiring MRSA infection among PV patients in the locality. Patients and methods This cross-sectional study included 54 PV patients. All patients were subjected to history taking, general, and dermatological examinations. Pemphigus disease area index score was calculated. Three swabs for bacterial culture and antibiotic sensitivity testing were obtained (one from vesicle or bulla, one from pustule, and the third from the nose). Results In all, 51 (94.4%) patients showed positive cultures for S. aureus either as nasal carrier, skin colonization, or skin infection. There was overlap as some patients showed more than one type of positive culture at the same time. Of the patients, 19 out of 51 patients (37.25%) had positive cultures for MRSA. All MRSA strains were sensitive to vancomycin. Also, they had good sensitivity to trimethoprim–sulfamethoxazole, amikacin, ciprofloxacin, and erythromycin, while all MRSA strains were resistant to cefoxitin and ampicillin. Hospitalization, previous antibiotics use in the last 4 weeks prior to this study, length of hospital stay, history of hospital-acquired infections, and community-acquired infections were significantly higher among MRSA-positive patients. Conclusion There is high MRSA infection/colonization among PV patients. MRSA responds to cheap antibiotics as trimethoprim–sulfamethoxazole, amikacin, and ciprofloxacin.